Foreign investment liberalization and incentives in selected Asia-Pacific Developing Countries:Implications for the health service sector in Nepal - Nephil Matangi Maskay; Rajan Krishna Panta; Bishnu Prasad Sharma (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2006)
The prime objective and main research questions of the study are: 1) What are the practices of service sector investment liberalization and incentives from selected developing countries, and 2) How those experiences can be applied to the investment liberalization and provision of incentives in the Nepalese services sector, with focus on the health service sector? It should be pointed out that a country's liberalizing strategy refers to a dynamic policy process through a flow in time; however since this study is presently limited to focus on a point in time (e.g. 2003), attention is given to FDI incentives in selected developing countries to tease out lessons of a broad service related investment (health) liberalization strategy.
Keywords: F1; 330